Africa in the Academy and the Study of International Relations in Spain: A Pending Subject (Comillas Journal of International Relations, 2019)
Little space that it occupies Africa in the study of International Relations, is explained for almost absence of African Studies in the curriculum, both in the basic education and in the bachelor´s degree and the master´s degree in Spain. It is still, therefore, conscious or unconsciously with the theories and eurocentrist visions or westerncentrists or the civilizing mission of Europe, to the margin of the dynamics and African conceptions of development. The realities of the globalization, in which it is not possible to exclude Africa, plead for the take in consideration the African Studies and the International African Relations, especially in the programs of Postdegree or Masters in Spain.
Keywords: international African relations; dynamic Africans; state; development; international society; postcolonialism; Sub-Saharan Africa